"FINTECH AND ISLAMIC BANKING: DERIVED FROM THE SEERAH OF PROPHET MUHAMMAD (PBUH)" (Qualitative Research Journal for Social Studies, 2026)
This study explores the role of Financial Technology (FinTech) in the development of Islamic banking and examines its relationship with the ethical teachings of the Seerah of Prophet Muhammad (PBUH). The research highlights how modern technologies such as blockchain, artificial intelligence, mobile banking, digital payment systems, and smart contracts are transforming Islamic financial institutions by improving efficiency, transparency, accessibility, and customer convenience. Islamic finance differs from conventional finance because it is based on Shariah principles that prohibit Riba (interest), Gharar (uncertainty), and unethical investments while promoting justice, honesty, and social welfare.The study further explains that the Seerah of Prophet Muhammad (PBUH) provides the ethical foundation for Islamic finance through principles such as trustworthiness, fairness, accountability, and transparency in business dealings. Islamic FinTech applications including crowdfunding, digital Zakat systems, blockchain-based Sukuk, and mobile banking contribute to financial inclusion and ethical economic development. However, Islamic FinTech also faces challenges such as cybersecurity risks, lack of standardization, regulatory issues, and Shariah compliance concerns. The research concludes that by integrating modern financial technologies with Islamic ethical values, Islamic banking can establish a transparent, socially responsible, and sustainable financial system for the modern world.